Tebet Eco Park’s potential as a new green open space in South Jakarta, Indonesia: an analysis - Yulita Suryantari; Hubertina Karolina Ngarbingan; Anisa Zahwa Akbara (STIE Pariwisata API Yogyakarta, 2022)
Tebet Eco Park is a new green open space in South Jakarta. The aims of this study is to analyze the condition of the facilities, potential visits, and provide suggestions for better Tebet Eco Park. The type of this study is descriptive qualitative research. The methods for collecting the data are observation, interviews, and documentation. The Miles & Huberman methodology, which consists of data reduction, data display, and data verification, is used to analyze research data. Tebet Eco Park contains eight different zones, and the facilities are in good and clean condition. In this research, eco park has good pull factors such as easy access, free prices, good facilities, and good staff service but does not guarantee that the revisit intention of visitors will always be positive. It is hoped that on weekends and holidays, eco park limit the number of visitors to enjoy the environment for a longer period of time. Visitors also want to come back if the place is not too crowded, and want to recommend Tebet Eco Park to their relatives. The first suggestion for organizers is to lower the visiting cap on weekends, and holidays. The second is to create an online visitor survey. The third is to construct a lactation area. The fourth is to create an activity calendar for the Eco Park.